Impact of spreading olive mill waste water on agricultural soils for leaching of metal micronutrients and cations. (July 2017) - Aharonov-Nadborny, R.; Tsechansky, L.; Raviv, M.; Graber, E.R.
Abstract: Olive mill waste water (OMWW) is an acidic (pH 4–5), saline (EC ∼ 5–10 mS cm −1 ), blackish-red aqueous byproduct of the three phase olive oil production process, with a high chemical oxygen demand (COD) of up to 220, 000 mg L −1 . OMWW is conventionally disposed of by uncontrolled dumping into the environment or by semi-controlled spreading on agricultural soils. It was hypothesized that spreading such liquids on agricultural soils could result in the release and mobilization of indigenous soil metals. The effect of OMWW spreading on leaching of metal cations (Na, K, Mg, Mn, Fe, Cu, Zn) was tested in four non-contaminated agricultural soils having different textures (sand, clay loam, clay, and loam) and chemical properties. While the OMWW contributed metals to the soil solution, it also mobilized indigenous soil metals as a function of soil clay content, cation exchange capacity (CEC), and soil pH-buffer capacity. Leaching of soil-originated metals from the sandy soil was substantially greater than from the loam and clay soils, while the clay loam was enriched with metals derived from the OMWW. These trends were attributed to cation exchange and organic-metal complex formation. The organic matter fraction of OMWW forms complexes with metal cations; these complexes may be mobile or precipitate, depending on the soil chemical and physical environment. Highlights: OMWW is frequently spread on agricultural land for disposal. OMWW effect on leaching of indigenous soil metals was tested in four soils. OMWW contributed metals to the soil solution. OMWW mobilized indigenous soil metals as a function of soil characteristics. Metal leaching was attributed to cation exchange and organic-metal complex formation.